Fast-Track Legislation in A State of Emergency: A Comparative Study of Indonesia and The United Kingdom - Bayu Aryanto (Journal of Constitutional and Governance Studies, 2025)
Every country has the potential to face emergency threats, such as natural disasters, riots, and even disease outbreaks. This will be why declaring and implementing a state of emergency needed to deal with future threats. An emergency forces the state to carry out its functions in an unusual way, including in forming laws that cannot be carried out properly. Special handling is needed in forming laws in emergency conditions. So far, laws regarding emergency conditions have been developed in Indonesia through Government Regulation in Lieu of Law. Meanwhile, the United Kingdom applies the Fast Track Legislation (FTL) method to handle its emergency conditions. Both have similarities and differences, each of which produces advantages and disadvantages. Various things that underlie the similarities and differences include history, legal systems, and government systems. The two mechanisms for forming laws have different qualities, based on the extent to which the principles of the rule of law and checks and balances are implemented. Keywords: Emergency, Procedure, Law, and Regulation. Abstrak Setiap negara berpotensi menghadapi ancaman darurat, seperti bencana alam, kerusuhan, bahkan wabah penyakit. Inilah sebabnya mengapa menyatakan dan menerapkan keadaan darurat diperlukan untuk menghadapi ancaman di masa depan. Keadaan darurat memaksa negara untuk menjalankan fungsinya dengan cara yang tidak biasa, termasuk dalam membentuk undang-undang yang tidak dapat dilakukan dengan baik. Penanganan khusus diperlukan dalam membentuk undang-undang dalam kondisi darurat. Sejauh ini, undang-undang mengenai kondisi darurat telah dikembangkan di Indonesia melalui Peraturan Pemerintah Pengganti Undang-Undang. Sementara itu, Inggris menerapkan metode Fast Track Legislation (FTL) untuk menangani kondisi daruratnya. Keduanya memiliki persamaan dan perbedaan, yang masing-masing menghasilkan kelebihan dan kekurangan. Berbagai hal yang mendasari persamaan dan perbedaan tersebut antara lain sejarah, sistem hukum, dan sistem pemerintahan. Kedua mekanisme pembentukan hukum memiliki kualitas yang berbeda, berdasarkan sejauh mana prinsip-prinsip supremasi hukum dan check and balances diterapkan. Keywords: Keadaan Darurat, Prosedur, Hukum dan Peraturan.